Black Sparrowhawk Accipiter melanoleucus breeding behaviour and reproductive success in KwaZulu-Natal, South Africa. (8th December 2017) - Wreford, Erin P; Hart, Lorinda A; Brown, Mark; Downs, Colleen T
Abstract : Black Sparrowhawk Accipiter melanoleucus breeding behaviour and nest success was determined using camera traps and field observations in KwaZulu-Natal, South Africa. Nest preparation was done predominantly by the male with incubation and brooding largely performed by the female. Brooding duration decreased with chick age, while feeding frequency and duration increased. Similarly, delivery of fresh leaf material to the nest site increased with chick age. Over the 2011 and 2012 breeding seasons respectively 74% and 41% of nests successfully fledged chicks, with the majority of these producing two offspring.